An integrative review of Indonesia’s quality of care - I Gede Juanamasta; Yupin Aungsuroch; Mary L. Fisher; Joko Gunawan; Abdulkareem S. Iblasi (Intelektual Pustaka Media Utama, 2023)
High-quality health care services would give good health outcomes to society. Nursing service is part of the quality-of-care process. The study aimed to investigate the quality of care in Indonesian hospitals over the last 20 years. The integrative review method was used, and 36 studies in Indonesia were analyzed, following the procedure: problem recognition, literature finding, data assessment, data review, and presentation of the results. Currently, the quality of care in Indonesia is low. The quality of care has increased over time in line with technology and science, and the factors which are related to quality have increased broader. Those factors are hospital management factors, nurse, and nursing organization the hospital management factors, including nurses staffing, environment, and job design. Nursing staffing factors are nursing shortage, workload, job satisfaction, burnout, and turnover. Meanwhile, work environment factors include supervision, empowerment, nurse-physician relationship, managerial, surveillance, and case management. Job design factors are nursing rounds, care delivery, competencies, training needs, roles, and documentation. Besides, personal factors are education, gender, ability/skills, and critical thinking. Therefore, the complicated factors related to nursing quality need further studies to explore whether they give significant results to improve quality of care.